Kinerja Mengajar dengan Sistem Work From Home (WFH) pada Guru di SMK Purnawarman Purwakarta - Busyra, Sarah; Sani, Lutfiah (Fakultas Tarbiyah, Institut PTIQ Jakarta, 2020)
This article tries to identify the teaching performance of teachers at SMK Purnawarman Purwakarta using the Work From Home (WFH) system during the Covid-19 pandemic. The population of this study is teachers at SMK Purnawarman Purwakarta which is 22 teachers. The method used mixture of Explanation Sequential, which is qualitative data can explain further more or strengthen the initial quantitative data. The results ot this study used descriptive statistical analysis with quantitative descriptive forms that are collaborated with descriptive qualitative data analysis. Data collection techniques using questionnaires, interviews and documentation in the form of school data. The results of this study showed the average performance of teachers in teaching using work from home system is only 50%. Overall, the performance results do not exceed the 70% limit. It happened because several factors are the half of the teachers do not understand some applications that used in teaching, also the distances caused the teachers face obstacles in interaction with students optimally.